Design, fabrication and perivascular implantation of bioactive scaffolds engineered with human adventitial progenitor cells for stimulation of arteriogenesis in peripheral ischemia. (24th March 2016) - Carrabba, M; De Maria, C; Oikawa, A; Reni, C; Rodriguez-Arabaolaza, I; Spencer, H; Slater, S; Avolio, E; Dang, Z; Spinetti, G; Madeddu, P; Vozzi, G
Abstract: Cell therapy represents a promising option for revascularization of ischemic tissues. However, injection of dispersed cells is not optimal to ensure precise homing into the recipient's vasculature. Implantation of cell-engineered scaffolds around the occluded artery may obviate these limitations. Here, we employed the synthetic polymer polycaprolactone for fabrication of 3D woodpile- or channel-shaped scaffolds by a computer-assisted writing system (pressure assisted micro-syringe square), followed by deposition of gelatin (GL) nanofibers by electro-spinning. Scaffolds were then cross-linked with natural (genipin, GP) or synthetic (3-glycidyloxy-propyl-trimethoxy-silane, GPTMS) agents to improve mechanical properties and durability in vivo . The composite scaffolds were next fixed by crown inserts in each well of a multi-well plate and seeded with adventitial progenitor cells (APCs, 3 cell lines in duplicate), which were isolated/expanded from human saphenous vein surgical leftovers. Cell density, alignment, proliferation and viability were assessed 1 week later. Data from in vitro assays showed channel-shaped/GPTMS-crosslinked scaffolds confer APCs with best alignment and survival/growth characteristics. Based on these results, channel-shaped/GPTMS-crosslinked scaffolds with or without APCs were implanted around the femoral artery of mice with unilateral limb ischemia. Perivascular implantation of scaffolds accelerated limb blood flow recovery, as assessed by laser Doppler or fluorescent microspheres, and increased arterial collaterals around the femoral artery and in limb muscles compared with non-implanted controls. Blood flow recovery and perivascular arteriogenesis were additionally incremented by APC-engineered scaffolds. In conclusion, perivascular application of human APC-engineered scaffolds may represent a novel option for targeted delivery of therapeutic cells in patients with critical limb ischemia.